APPLICATION OF MULTIPLICATIVE RANDOM NUMBER GENERATOR (MRNG) ALGORITHM IN BUILD SEMESTER EXAM APPLICATION - Nasution, Yusuf Ramadhan; Fakhriza, M; Sitanggang, Merlin (ZERO: Jurnal Sains, Matematika dan Terapan, 2022)
In the world of education, exams are used to measure how well students have achieved their educational goals. This allows students to determine their level of understanding of the subject they  are pursuing. If the results are found to be suboptimal, the learning process should be improved. A semester exam is an activity conducted to assess a student's development during the completed training period. MTs Persiapan Negeri 4 Medan is one of the educational institutions that conducts semester exams according to the Paper Pencil Test (PPT) model exam system. PPT is a traditional form of administration as all students are given the same test tasks. However, this review system has its drawbacks. The drawback of the question lies in the procurement of exam questions and answer sheets, which wastes paper and takes a lot of time. Also, their administration requires a lot of manpower to proctor the exams and specialized staff to revise the answer sheets and prepare the exam results. In this study, we will implement a Multiplicative Random Number Generator (MRNG) method to create a mobile-based semester exam application on MTs Persiapan Negeri 4. The designed application aims to overcome problems encountered in traditional exams, so there is no need to procure questionnaires or answer sheets, and no special staff is required to correct answer sheets